Proactive Pharmacovigilance and Risk Management - Raine, J; Wise, L; Talbot, J; Aronson, J (John Wiley and Sons, 2012)
Increasing concerns about adverse drug reactions and the necessary withdrawal from the market of effective medicines because of such reactions have led to a more proactive approach to risk management than hitherto. A risk management system is a set of pharmacovigilance activities and interventions designed to identify, characterize, prevent, or minimize risks relating to medicinal products, and assessment of the effectiveness of those interventions. The aim of such systems is to ensure that the benefits of a medicine or group of medicines exceed the risks of harms by the greatest achievable margin for the individual patient and for the target population in general. A risk management plan consists of a safety specification (a summary of the important identified risks of a medicinal product, important potential risks, and important missing information), a pharmacovigilance plan, evaluation of the need for risk minimization, and, if necessary, a risk minimization plan. Methods of risk minimization include letters to health-care professionals, prescribing guides, dispensing guides, patient brochures, and training programmes. Specific problems are posed by the use of medicines in healthy people and new problems with old medicines. The DoTS classification of adverse drug reactions suggests a potential novel strategy for action when a marketed product causes a new adverse reaction, based on four questions: Can a susceptible subpopulation be distinguished as such before treatment? Is a monitoring strategy practicable? Is a protective strategy possible? To what extent does the benefit outweigh the harm in the population © 2012 John Wiley and Sons, Ltd.